PICEA ABIES: GERMINATION AND DEVELPOMENT OF SEEDLINGS IN DIFFERENT SUBSTRATE TYPES AND TREATMENTS - Cornel Negrușier; Orsolya Borsai; Steluța-Maria Sîngeorzan; Ervin Kremer; Alexandru Colișar; Vasile Ceuca (Agricultura)
The aim of our research was to investigate how different substrate type and biostimulants can influence the process of germination and seedling development of spruce (Picea abies). To carry out this study, seeds from four different location from Romania were used. For the germination and development of spruce seedlings, five distinct types of substrate were used: oligotrophic peat, peat and perlite mixture, perlite, sand and sand and perlite mixture. In the case of germination stimulation, two types of biostimulants were applied, Atonik and Cropmax, and the results were compared with a control variant, without treatment. The results highlighted significant differences depending on the type of substrate and treatment, providing valuable information about the optimal conditions for germination and growth of the seedlings. The results showed that S2 substrate (peat+perlite) proved to be the most effective for seed germination of spruce seeds, achieving remarkable results when combined with Atonik treatment. For seeds from the Miraj provenance, the germination rate reached 92%, highlighting the advantages of using this type of substrate to optimize the germination process and seedling development.